An analytical model for mountain wave in stratified atmosphere (MAUSAM, 1998)
An analytical, two-dimensional computer model has been developed for real time prediction of 'mountain wave due to Principal mountains over Kashmir valley. Simulation of the L2 profile has been made with realistic, non-zero values at higher levels and exponentially decreasing values at lower levels. Unlike Doos (1961), present solution has no restriction on the value of wave number (k). Validity of the model has been tested with the satellite observed waves in seven cases and actual aircraft report in one case.